2006
DOI: 10.2166/wqrj.2006.045
|View full text |Cite
|
Sign up to set email alerts
|

Impact des rejets industriels sur l'environnement : cas de l'accumulation du chrome dans les différents compartiments aquatiques le long du littoral Casablanca – Mohammadia

Abstract: En absence de normes de rejet, les rejets industriels au Maroc sont rejetés dans le milieu naturel, en particulier marin, sans aucun traitement préalable. Aussi, l'objectif du présent travail est d'étudier l'impact des rejets industriels riches en chrome au niveau des différents compartiments aquatiques (mollusques, poissons, algues et sédiments) le long de huit stations de prélèvements sur le littoral entre Casablanca et Mohammadia, durant une période de cinq années (été 1998 – printemps 2002); en plus, cette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
2
1
0
Order By: Relevance
“…The maximum average concentrations for Al (1215.0 mg/kg), As (14.2 mg/kg) and Li (1.74 mg/kg) were observed in the winter season, while the minimum mean contents for Al (494.9 mg/kg), As (8.74 mg/kg), and Li (1.46 mg/kg) were indicated in the summer period. Similar results have been found by many researchers [23][24][25][26][27][28][29]. Bouthir et al [25] indicated in the Moroccan Atlantic Ocean, higher contents of metallic elements in tissues of M. galloprovincialis during the wet period (winter), whereas lower contents were observed in the hot period (summer).…”
Section: Heavy Metal Analyzessupporting
confidence: 88%
See 2 more Smart Citations
“…The maximum average concentrations for Al (1215.0 mg/kg), As (14.2 mg/kg) and Li (1.74 mg/kg) were observed in the winter season, while the minimum mean contents for Al (494.9 mg/kg), As (8.74 mg/kg), and Li (1.46 mg/kg) were indicated in the summer period. Similar results have been found by many researchers [23][24][25][26][27][28][29]. Bouthir et al [25] indicated in the Moroccan Atlantic Ocean, higher contents of metallic elements in tissues of M. galloprovincialis during the wet period (winter), whereas lower contents were observed in the hot period (summer).…”
Section: Heavy Metal Analyzessupporting
confidence: 88%
“…Similar results have been found by many researchers [23][24][25][26][27][28][29]. Bouthir et al [25] indicated in the Moroccan Atlantic Ocean, higher contents of metallic elements in tissues of M. galloprovincialis during the wet period (winter), whereas lower contents were observed in the hot period (summer). The seasonal fluctuations in metal levels in Al Hoceima coast may be due to a combination of factors, directly related to weight (reproductive cycle, sexual maturity, abundance of food and environmental conditions) [30,31], but also others, independent, such as the biogeochemical cycle change and the bioavailability of metals in the seawater [32].…”
Section: Heavy Metal Analyzessupporting
confidence: 88%
See 1 more Smart Citation